Prevention of the inhibitory effect of intraperitoneal 5-FU on intestinal anastomosis by zinc - Ali Rıza TÜMER,; Nuri Aydın KAMA,; Sevda F. MÜFTÜOĞLU,; Cenap DENER,; Leyla TÜMER,; Atilla DAĞDEVİREN, (Turkish Journal of Gastroenterology, 2019)
-